1995
DOI: 10.1128/jcm.33.10.2637-2642.1995
|View full text |Cite
|
Sign up to set email alerts
|

Ribotyping for use in studying molecular epidemiology of Serratia marcescens: comparison with biotyping

Abstract: Ribotyping carried out with a nonradioactive probe (acetylaminofluorene ribosomal RNA kit I from Eurogentec, Seraing, Belgium) was performed for the characterization of 139 hospital strains of Serratia marcescens. These strains, which belonged to 11 biotypes and 1 nontypeable group, were isolated in seven hospitals in Belgium between 1986 and 1992. EcoRI and HindIII were used to obtain cleavage patterns. Analysis of the results produced 27 different patterns with EcoRI and 23 patterns with HindIII. Typeability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Ribotyping has been used for the study of many bacterial species responsible for nosocomial infections (6,11) and also for different species of the genus Salmonella (12,19,30,35). In our study, ribotyping revealed an identical pattern ( Fig.…”
supporting
confidence: 60%
“…Ribotyping has been used for the study of many bacterial species responsible for nosocomial infections (6,11) and also for different species of the genus Salmonella (12,19,30,35). In our study, ribotyping revealed an identical pattern ( Fig.…”
supporting
confidence: 60%
“…(iii) Ribotyping. Ribotyping with EcoRI and HindIII with a nonradioactive probing system (acetylaminofluorene rRNA Kit I from Eurogentec, Seraing, Belgium) was carried out as reported earlier (1).…”
Section: Methodsmentioning
confidence: 99%
“…Ribotyping was performed with the restriction enzyme PvuII by using a [␣-32 P]dCTP-labeled gene probe from Escherichia coli 16S-plus-23S RNA. Strains that differed by more than two bands were considered to be different clones, while single band differences were interpreted as subtypes (2).…”
mentioning
confidence: 99%